GIS TECHNIQUES FOR MAPPING OF WIND SPEED OVER IRAQ - & Al-Timimi, Adeeb (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to use GIS techniques in climate studies. Analysis of monthly wind speed data for the period 1981 to 2017, and mapping of monthly, seasonal and annual wind speed in Iraq has been investigated in this study. The area of study was divided into three regions. the results of  Mann Kendall test of the middle and southern region reveal a significant decreasing trend in the months of the summer season. While positive trends of mean wind speed were found in the northern region for the whole period. Wind speed value reaches its highest value in (Jun and July), and the lowest value of wind speed was in December.  Seasonal wind speeds show the highest values recorded in the summer and spring seasons and the lowest in the autumn and winter seasons. Wind speed maps were obtained using IDW techniques in G I S, the results show that the annual average of wind speed in the northern, middle and southern regions was 2.7 m/s, 3.6 m/s and 4.1 m/s respectively. While the annual average of wind speed in the study area "Iraq" was 3.6 m/s. The winds were low in the northern region compared to the middle and southern regions. The wind speed maps show the appropriate sites for the installation of wind turbines.